731 Single centre experience tricuspid valve transcatheter edge to edge repair. (8th December 2021) - Paolucci, Luca; Nusca, Annunziata; Cammalleri, Valeria; Nobile, Edoardo; De Filippis, Aurelio; Vitez, Luka; Carpenito, Myriam; Ricottini, Elisabetta; Melfi, Rosetta; Cocco, Nino; Mangiacapra, Fabio; Gallo, Paolo; et al.
Abstract: Aims: Severe tricuspid valve regurgitation (TVR) is critically associated with an increased risk of morbidity and mortality, surgical treatment is limited by high perioperative risk. In these patients, transcatheter edge to edge valve repair (TEER) is progressively recognized as an effective treatment strategy. The aim of this work is to report the single centre experience procedural results and clinical outcomes in 'real-world' patients suffering TVR treated with the TriClip™ device (Abbott Vascular, Santa Clara, California). Methods: From January up to July 2021, we screened 30 patients with severe TR, among which 8 were treated with TEER. All patients underwent cardiac computerized tomography and both transesophageal and transthoracic echocardiography, with the purpose to identify a dedicated grasping strategy. TEER was performed through right common femoral vein access, advancing a 24 F steerable guiding catheter (SGC) in the right atrium. Following, the TriClip delivery system was advanced and positioned over the valve centroid and, once oriented, the clip was opened. Under fluoroscopic and transesophageal monitoring, the clip was advanced in the right ventricle and pulled back to grasp the target leaflets. Following echocardiographic control, the clip was released. Results: Procedural success, defined as a significative reduction of the regurgitation's severity, was achieved in all patients. No procedural or in-hospital adverse events were reported. At 30 days follow-up, all patients were alive and no further hospitalizations occurred. Conclusions: In our single centre experience, TEER appeared to be a valid and feasible therapeutic option in patients with severe TVR. Multicentre prospective studies are mostly needed to assess the long terms outcomes of TEER in these patients, with the purpose to introduce in the clinical practice a valid alternative to the highly risk surgical option.